EXPERIENTIAL FUNCTION IN ENGLISH ZONE TEXTBOOK - Ashari, Erwin (English Department, University of Riau Kepulauan, Batam,Indonesia, 2017)
The aim of this study was to identify the experiential function aspect found in conversation text. They were Process, Participant and Circumtance. There were five chosen conversation texts then they were broken up into single clauses. They were taken from conversation text or clauses found in conversation text in student’s English text book: English Zone. It was found that the conversation texts were categorized as simple text, because they were dominated by the simple cluase. The most dominant Process were Material Process (36.80 %). and Relational Process, meanwhile for Participant, the dominant were Attribution (28.22 %), Attribute (19.78%), Goal (17.16%), Actor (15.30%) and Carrier (14.93%), the dominant Circumtances in conversation texts were Location Spatial (28.81%), Manner (22.03%), Location Temporal(20.34%). Based on the findinds, it could be said that the conversation texts in those book refered to the natural conversation. there were three kinds of text found, they were Doing text, Saying text and Being text. The conversation texts were dominated by the Doing and Being texts. Doing text means that the texts were dominated by the Material Process, and Being text means that the texts were dominated by the Verbal ProcessKeywords: Process, Participant, Circumtance, Being, Doing, Saying Texts